A Pragmatic Study of Deixis in Imran Khan's Speech at the United Nations General Debate (The Journal of Educational Development, 2021)
Language is one of the tools for communication. One of the functions of the language is the referential function which points out something in an immediate situation. Deixis is one of the pragmatics branches that is essential to learn about pointing person, time, place, discourse, and social in a contextual event, especially delivering a speech in an international forum such as the United Nations. This pragmatic analysis study investigates the most dominant deixis used and reasons why used of deixis in Imran Khan’s address at United Nations General Debate in 2019. The researcher uses qualitative as the design of the study. Furthermore, the researcher observed a video recording for the instrument of the study. The findings revealed that Imran Khan used time deixis dominantly in his speech. The time deixis appeared 554 times. He used 41.81% of it for the full address. He used deixis to show defines his feeling, persuade, and reveal ideological bias. Therefore, it is essential to consider the context of the speech to avoid the misinterpretation of the utterances.